Evaluating browsing damage to selected taxa in a trial plantation within the Lungmanis Forest Reserve, Sabah, Malaysia - RICHARD J. MAJAPUN; VIVIANNYE PAUL; MOHD. AMINUR FAIZ SUIS; EYEN KHOO; VERONICA S. GUANIH; PANG KAT NYEN KELVIN; CHEN THAU EN; MARIA AJIK (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Majapun RJ, Paul V, Suis MAF, Khoo E, Guanih VS, Kelvin PKN, En CT, Ajik M. 2024. Evaluating browsing damage to selected taxa in a trial plantation within the Lungmanis Forest Reserve, Sabah, Malaysia. Biodiversitas 25: 3540-3554. The study assessed the impact of wildlife pests on seven tree taxa, including Acacia crassicarpa, Eucalyptus pellita, Falcataria moluccana, Khaya ivorensis, Neolamarckia cadamba, Terminalia copelandii, and Swietenia macrophylla, in trial plantations within Sabah's Lungmanis Forest Reserve, Sabah, Malaysia. Browsing damage was measured for all taxa at two time points (t1 and t2) using three indices (H-Index, S-Index, and PS-Index). The study revealed that E. pellita, A. crassicarpa, and K. ivorensis resisted browsing damage. At the same time, other species, such as N. cadamba and F. moluccana, suffered significant damage, with tree height losses between 50% and 70% due to wildlife pest activity. The study recorded high damage intensity for the PS-Index in the "Shooting" category. It also showed that subplot configurations with open (D) and fenced (A) plots exhibited similar levels of "Shooting," uncovering that some wildlife pests, like Sambar deer (Rusa unicolor (Kerr, 1792)) and pig-tailed macaques (Macaca nemestrina (Linnaeus, 1766)), were not entirely deterred by fencing and repeatedly browsed their preferred taxa. Additionally, N. cadamba was more susceptible to pest defoliators following the browsing damage than other taxa. The research highlights the limitations of fencing as a mitigation measure for wildlife-induced tree damage and underscores the need for a comprehensive wildlife management approach in forest plantations. This includes understanding wildlife behavior and human impact factors beyond population density and emphasizes the importance of species selection and plot configuration in managing wildlife-induced damage.